Curie temperatures of synthetic titanomagnetites in the Fe-Ti-O system: effects of composition, crystal chemistry, and thermomagnetic methods - Lattard, Dominique; Engelmann, Ralf; Kontny, Agnes; Sauerzapf, Ursula (Journal of geophysical research. Solid earth, 2006)
The present study is aimed at improving the calibration of the compositional dependence of the Curie temperature (TC) of titanomagnetite (Tmt) on the basis of temperature-dependent magnetic susceptibility (χ-T) curves measured on synthetic Tmts in the Fe-Ti-O system. In order to assess the possible influence of high-temperature cation vacancies onto the TC values, we have synthesized two types of assemblages in subsolidus conditions at 1 bar, 1100°C and 1300°C, under controlled oxygen fugacity conditions. Tmts synthesized in equilibrium with ilmenite-hematitess (Ilmss) are expected to have the highest vacancy concentrations, those in equilibrium with wüstite (Wus) the lowest. The composition and homogeneity of the synthetic Tmts were carefully checked with a scanning electron microscope (SEM) and an electron microprobe (EMP). TC was determined from χ-T curves using a kappabridge and, for comparison, from Ms-T curves measured with a variable field translation balance. Our data set shows systematically higher TC values for Tmt coexisting with Ilmss than for Tmt coexisting with Wus. Most χ-T curves are nonreversible, whereby the largest ΔTC (40 K) concern Tmt(+Ilmss) of intermediate compositions synthesized at 1300°C. Nonreversibility is interpreted as reflecting cation reordering in Tmt during the high-temperature χ-T measurements. TC values obtained from Ms-T curves are higher than those obtained from the χ-T curves, whereby the difference regularly increases (up to 40 K) with increasing Ti content, up to XUsp = 0.6. Our new calibration curves are suitable to retrieve Tmt compositions in basalts that were rapidly cooled and not oxidized by deuteric or hydrothermal fluids.
Gesehen am 06.10.2020